Promising utilization of fly ash as an eco-friendly sustainable additive for enhancement in flame retardancy of composite production: A review - N. A., Latip; Azizul Helmi, Sofian; Mohd Faizal, Ali; Siti Natrah, Ismail; D. N. D., Idris (IOP Publishing, 2020)
Fly ash as one of the industrial by-product generated from the coal-based power station will eventually recognized as an environmental pollutant due to their enrichment in potentially toxic trace elements. Hundreds of thousand tons of fly ash every year exist alone were expected from the growth in power plants that use coal as the source of fuel. The present waste is widely been used in concrete industries to replace the usage of cement which is can minimize carbon dioxide footprint, but most will go straightly to the landfill or dump that will be one of the significant matter in environmental concerns and also will soon to be costly due to long term financial burden of maintenance. An economically viable solution to this problem has been proposed by utilization of fly ash as reinforcement in polymer matrix based composite production focusing on construction industry. Several studies proposed that fly ash has great potential as flame retardant in order to develop fire proof products even though not been much examined. This paper will emphasize on reviewing about properties of fly ash with its possible composition and characteristic that can help in fire controlling.